Community Involvement and Attachment in Developing Panundaan Pioneer Tourism Village: Applying Extended Social Exchange Theory - Sobarna, Aditia; Primanty, Annisa; Novianti, Evi; Yustikasari, Yustikasari (Jurnal Komunikasi, 2024)
This study examines the impact of community involvement and attachment on the development of pioneer tourism villages, specifically focusing on Panundaan Tourism Village in West Java, Indonesia. Employing a quantitative methodology, the research utilizes structured questionnaires to gather data from residents, analyzing their perceptions of the costs and benefits associated with tourism development. Utilizing Social Exchange Theory as a theoretical framework, this study seeks to understand how perceived costs and benefits influence community support for tourism initiatives and how these perceptions correlate with residents' life satisfaction. The analysis, conducted through Structural Equation Modeling, reveals that deeper community attachment enhances perceived benefits but also heightens awareness of costs. The findings highlight the complex interplay between community involvement, perceived benefits, and life satisfaction, offering insights into strategies for sustainable tourism development in pioneer tourism villages.